Synthesis, Characterization and Analytical Applications of Copper(II) N-Hydroxyamidines Complex - Chandra Tiwari, Sushil; Mohabey, Hemlata (Asian Journal of Chemistry, 2016)
Copper(II) reacts with N-hydroxy-N-(o-chloro)phenyl-N'-(2,6-dimethyl)phenyl benzamidine hydrochloride and forms buff precipitate in the pH range 2.5–10.0, which is insoluble in water and most of the organic solvents. The reaction is highly selective at pH 3.0–4.5. The analytical data indicate metal to ligand ratio 1:2. The conversion factor 0.0837 is very small, which makes the method applicable for the determination of micro quantity of copper(II). Most of the common ions including Mn(II), Ni(II), etc., do not interfere with the determination. The method has been successfully applied for the determination of copper(II) in alloys and biological samples.